2003
DOI: 10.1038/nbt918
|View full text |Cite
|
Sign up to set email alerts
|

Principles of transcriptional control in the metabolic network of Saccharomyces cerevisiae

Abstract: Cellular networks are subject to extensive regulation, which modifies the availability and efficiency of connections between components in response to external conditions. Thus far, studies of large-scale networks have focused on their connectivity, but have not considered how the modulation of this connectivity might also determine network properties. To address this issue, we analyzed how the coordinated expression of enzymes shapes the metabolic network of Saccharomyces cerevisiae. By integrating large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
229
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(241 citation statements)
references
References 25 publications
10
229
1
1
Order By: Relevance
“…In general, the population of within-pathway comparisons contained a higher proportion of high-confidence (low p and high r 2 ) results than did comparisons involving genes from different pathways (Table I). Thus, we found that genes annotated as belonging to the same pathway tend to be more tightly coexpressed than genes from different metabolic pathways, a result that is consistent with results obtained from similar studies in yeast (Ihmels et al, 2004b). Interestingly, we also found that the relative proportion of highconfidence coexpression relationships is also higher among positively coexpressed genes than among negatively coexpressed genes.…”
Section: Genes Belonging To the Same Pathway Are Coexpressedsupporting
confidence: 81%
See 2 more Smart Citations
“…In general, the population of within-pathway comparisons contained a higher proportion of high-confidence (low p and high r 2 ) results than did comparisons involving genes from different pathways (Table I). Thus, we found that genes annotated as belonging to the same pathway tend to be more tightly coexpressed than genes from different metabolic pathways, a result that is consistent with results obtained from similar studies in yeast (Ihmels et al, 2004b). Interestingly, we also found that the relative proportion of highconfidence coexpression relationships is also higher among positively coexpressed genes than among negatively coexpressed genes.…”
Section: Genes Belonging To the Same Pathway Are Coexpressedsupporting
confidence: 81%
“…Connectivity in the yeast (Saccharomyces cerevisiae) metabolic network has been explored using gene coexpression data and structural information about the pathways; these studies have revealed fundamental insights into the general properties of metabolic gene networks in eukaryotes (DeRisi et al, 1997;Ihmels et al, 2004b). One early result was that functionally related genes are often coexpressed, and this observation has provided strong motivation for the adoption of expression microarrays in biological research (DeRisi et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This concept implies that cellular functionality is organized in a set of functional modules, which consequently are organized in a few large modules, which in turn can be grouped into even larger modules (Jeong et al, 2000;Ravasz et al, 2002;Ihmels et al, 2004). The hierarchical modularity of metabolic network organization would allow robust, error-tolerant, and energetically efficient functioning of biological systems.…”
Section: Full Spectral Alignment Enables Unbiased Comparative Metabolmentioning
confidence: 99%
“…However, researchers have yet to do this comparison with regulatory networks. Of all biological networks, regulatory networks are of particular interest, because to some degree they act as the master control system for the cell, tightly coordinating the expression of all genes (13)(14)(15). From a graph-theoretical point of view, regulatory networks are different from interaction networks in that they are directed.…”
mentioning
confidence: 99%